Accessibility, accountability, affordability: healthcare policy in orthopedic trauma - Genova, Renee C. (Curr Rev Musculoskelet Med, 2017)
PURPOSE OF REVIEW: This review provides historical background on trauma care in the USA and summarizes contemporary trauma-related health policy issues. It is a primer for orthopedic surgeons who want to promote improvements in research, delivery, and cost reduction in trauma care. RECENT FINDINGS: As of 2010, funding for trauma research accounted for only 0.02% of all National Institutes of Health research funding. This is disproportionate to the societal burden of traumatic injury, which is the leading cause of death and disability among people aged 1 to 46 years in the USA. The diagnosis-related group model of hospital reimbursement penalizes level-I trauma centers, which typically treat the most severely injured patients. Treatment of traumatic injury at level-I and level-II trauma centers is associated with lower rates of major complications and death compared with treatment at non-trauma centers. Patient proximity to trauma centers has been positively correlated with survival after traumatic injury. Inadequate funding has been cited as a reason for recent closures of trauma centers. SUMMARY: Orthopedic surgeons have a responsibility to engage in efforts to improve the quality, accessibility, and affordability of trauma care. This can be done by advocating for greater funding for trauma research; choosing the most cost-effective, patient-appropriate orthopedic implants; supporting the implementation of a national trauma system; leading high-quality research of trauma patient outcomes; and advocating for greater accessibility to level-I trauma centers for underserved populations.